MENETAS JALAN BARU STUDI PENGEMBANGAN MASYARAKAT ISLAM - Suraji Suraji (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
The concept of community development can be viewed as a process because the involved activities moves from one stage to another or from a specific situation to the next one. The relevant study in it is the study of Islamic Community Development which is in line with the role of Higher Education College. That is to functioning Tri Darma consisting of education, research and community services. Such view certaintly becomes real hope if it can implemented seriously. Another factor is that the specialization of knowledge as the basis of intellectual and expertise specially the study of community development have an important and strategic place in the globalization era in terms of political, economic, social and cultural rights.